STRATEGIC MANAGEMENT OF ENTERPRISE DEVELOPMENT THROUGH USE-STATE OF LEAN-TECHNOLOGIES AT REGIONAL AND STATE LEVELS: Array - Dymchenko, O.; Rudachenko, O.; Prasol, V.; Dril, N. (Municipal economy of cities. Series: «Economy science», 2021)
The article considers the strategic management of enterprise development on the basis of the latest technologies of lean production - lean technologies. According to the results of the study, the following conclusions were established that the introduction of the "Lean Production" system is the transition of the enterprise to a new, better level, which involves the involvement of all employees of the construction company. At the same time, active participation is provided by both material incentives (for implemented or approved before implementation proposals) and intangible (for example, the opportunity to participate in the management of the enterprise, the implementation of their ideas, career growth, etc.). This should become a separate element of the system of incentives and motivation of staff operating in the enterprise. The main question that Ukrainian companies ask first of all when implementing the provisions of lean production within the quality management system is the choice of the necessary tools that will help achieve significant results and increase the efficiency of the enterprise. The structure of the Ukrainian economy is dominated by industries that are characterized by continuous production processes: metallurgy, oil and gas, mining, paper industry, etc. The success of any company is largely determined by the quality and value of goods and services provided. To succeed in its activities, to achieve competitive quality and competitive prices of manufactured goods and services, the company must ensure the creative work of the whole team, the interaction of its constituent elements. In modern conditions, the competitiveness of the company in the market is the main criterion for production efficiency, evaluation of the results of the management system, and it can be achieved only through the efforts of the company's staff as a whole. Product quality management of a production enterprise today is an extremely important issue for domestic enterprises and deserves special consideration. Thus, using one of the initial tools of "lean production", it was possible to increase the efficiency of the production process. As soon as the company correctly determines the value, diverts the entire flow of value creation, begins to continuously add value to the product at each stage of the flow, all participants in the process will understand that the process of improvement can be endless. You can reduce labor costs, time, production space, cost and number of errors, while creating a product that is closer and closer to the ideal, which is important for the construction of residential buildings. These measures will provide an opportunity to improve economic relations in enterprises.